The snow leopard - Matthiessen, Peter 1927-2014 (Penguin Books, 1996)
When Matthiessen went to Nepal to study the Himalayan blue sheep and , possibly, to glimpse the rare and beautiful snow leopard, he undertook his five-week trek as winter snows were sweeping into the high passes. This is a radiant and deeply moving account of a "true pilgrimage, a journey of the heart".
Originally published: New York : Viking Press, 1978. - Includes bibliographical references (p. [325]-330) and index
Keywords: Geschichte 1900-2000; Authors, American -- 20th century -- Biography; Biologists -- United States -- Biography; Natural history -- Himalaya Mountains; Reisebericht; Expedition; Schneeleopard; USA; Himalaya Mountains -- Description and travel; Nepal; Himalaja; Dolpo; Biografie